EX OFFICIO HAKIM DALAM MENEMUKAN HUKUM - Lubis, Fauziah; Devi, Delima Puspita; Siregar, Risnawati; Sari, Fitria Novita; Pamungkas, Putra; Anindya, Putri Rizka; Varissa, Rizka Dina (Gapenas Publisher, 2025)
This study aims to analyze in depth the role of ex officio judges in the process of finding the law through their knowledge, especially as part of the consideration of evidence in civil procedural law. The problems studied include the position of judges' knowledge in the civil evidence system and the extent to which its use can be legally justified. The background of this study is based on the still widespread practice of using judges' personal knowledge in deciding cases, although normatively the evidence in civil procedural law has been determined in a limited manner in article 164 HIR. Judges' knowledge is often used unwritten as a basis for consideration, which has the potential to cause legal uncertainty. The method used is a juridical-normative approach with data collection techniques through literature studies of legal literature and court decisions. The results of the study show that although it is no longer explicitly regulated in positive law, judges' knowledge is still used as a basis for assessing legal facts. This shows the need for an update to civil procedural law in order to provide clear limitations on the use of judges' victories in the ex officio context.